2004
DOI: 10.1023/b:lahu.0000046436.36228.71
|View full text |Cite
|
Sign up to set email alerts
|

An examination of jury verdicts for evidence of a similarity-leniency effect, an out-group punitiveness effect or a black sheep effect.

Abstract: Archival data from cases adjudicated by jury in El Paso and Bexar County, Texas, were used to test whether a similarity-leniency effect, an out-group punitiveness effect, or a black sheep effect (BSE; J. M. Marques, V. Y. Yzerbyt, & J. P. Leyens, 1988) influenced jury decisions. Defendant ethnicity, jury ethnic composition, and strength of evidence against the defendant were coded for 418 closed noncapital, felony cases to test their impact on trial verdicts and sentence lengths. Results indicated complex rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 63 publications
(36 citation statements)
references
References 21 publications
2
32
0
Order By: Relevance
“…The literature synthesis provided above indicates that Hispanics have a unique perspective that is not always in agreement with other ethnic minorities, and in some instances is more in agreement with the attitudes of the Caucasian majority (Boots et al, 2004;de la Garza & DeSipio, 2001;Garcia & Cao, 2005;Ong & Jenks, 2004;Reitzel et al, 2004;Taylor & Hosch, 2000). Together, the demographic shift and the results of the studies reviewed here amplify the need for Hispanics to be studied as a unique ethnic group.…”
Section: Quantitative Analysismentioning
confidence: 69%
See 2 more Smart Citations
“…The literature synthesis provided above indicates that Hispanics have a unique perspective that is not always in agreement with other ethnic minorities, and in some instances is more in agreement with the attitudes of the Caucasian majority (Boots et al, 2004;de la Garza & DeSipio, 2001;Garcia & Cao, 2005;Ong & Jenks, 2004;Reitzel et al, 2004;Taylor & Hosch, 2000). Together, the demographic shift and the results of the studies reviewed here amplify the need for Hispanics to be studied as a unique ethnic group.…”
Section: Quantitative Analysismentioning
confidence: 69%
“…Subsequent studies have found that Hispanic majority juries gave defendants shorter recommended sentences and earlier parole than Caucasian majority juries (Perez et al, 1993). Similarly, Taylor and Hosch (2000) found that juries comprised of a majority of Hispanic jurors render less severe verdicts than predominately ''non-Hispanic juries.'' The categorization of the control as ''non-Hispanic'' confounds the ability to make cross-cultural comparisons; however, the results are consistent with other research, that juries composed primarily of Hispanic jurors were more lenient than were juries with a majority of Caucasian jurors.…”
Section: Jury Decision Making: Hispanics Compared With Caucasiansmentioning
confidence: 99%
See 1 more Smart Citation
“…Individuals use these mechanisms to maintain a positive self-image and these mechanisms are most often referred to as "ingroup bias." In the current context, it is important to examine ingroup/outgroup theories as they can play a critical role in jury decision-making, particularly when examining how jurors may categorize the defendants or victims involved in a trial (Taylor & Hosch, 2004). Two predominant theories have emerged that attempt to explain how these ingroup/outgroup mechanisms apply in the context of jury decision-making: (1) similarity-leniency hypothesis and Many juror decision-making studies have looked at the first of these theories, similarityleniency hypothesis, which proposes that jurors are more lenient toward defendants who are similar to themselves, rather than dissimilar (Abwender & Hough, 2001;Kerr, Hymes, Anderson, & Weathers, 1995;Sommors & Ellsworth, 2000;Van Proojien, 2006;Wuensch, Campbell, Kesler, & Moore, 2002).…”
Section: Ingroup/outgroup Theory and Assignment Of Punishmentmentioning
confidence: 99%
“…In a hate crime trial, this may indicate that jurors would view defendants more harshly if they consider them as a member of their ingroup and therefore increase the likelihood of assigning a harsher sentence. Taylor and Hosch (2004) also conducted a study that examined archival data from 418 felony cases whose outcomes were obtained through a trial by jury. The study included cases that involved defendants who were identified as either Hispanic or Caucasian and examined whether jury verdicts showed evidence of a similarity-leniency effect, an out-group punitiveness effect, or a black sheep effect.…”
Section: Black Sheep Effectmentioning
confidence: 99%